2021
DOI: 10.3389/fimmu.2021.701811
|View full text |Cite
|
Sign up to set email alerts
|

Whole Blood Interferon γ Release Is a More Sensitive Marker of Prior Exposure to Coxiella burnetii Than Are Antibody Responses

Abstract: For the zoonotic disease Q fever, serological analysis plays a dominant role in the diagnosis of Coxiella burnetii infection and in pre-screening for past exposure prior to vaccination. A number of studies suggest that assessment of C. burnetii-specific T-cell IFNγ responses may be a more sensitive tool to assess past exposure. In this study, we assessed the performance of a whole blood C. burnetii IFNγ release assay in comparison to serological detection in an area of high Q fever incidence in 2014, up to sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…Samples from n=98 de-identified adult blood bank donors from the Amsterdam/Rotterdam area (The Netherlands) with unknown prior exposure to C. burnetii were obtained in November 2020 from the Sanquin Blood bank ( Table 1 ) ( 24 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples from n=98 de-identified adult blood bank donors from the Amsterdam/Rotterdam area (The Netherlands) with unknown prior exposure to C. burnetii were obtained in November 2020 from the Sanquin Blood bank ( Table 1 ) ( 24 ).…”
Section: Methodsmentioning
confidence: 99%
“…unknown prior exposure to C. burnetii were obtained in November 2020 from the Sanquin Blood bank (Table 1) (24).…”
Section: Ethics Statementmentioning
confidence: 99%
“…Recently, it has been reported that C. burnetii -specific T-cell IFN-γ release may represent a sensitive and long-lasting marker of past C. burnetii exposure ( Scholzen et al., 2021 ). The evaluation of cell-mediated responses to Coxiella through IFN-γ release assay (IGRA) could be very useful to detect past infections, since cellular response persists also in sero- and skin test-negative individuals ( Schoffelen et al., 2014a ; Schoffelen et al., 2013 ; Scholzen et al., 2021 ).…”
Section: Current Diagnostic Approaches For Coxiella Burnetiimentioning
confidence: 99%
“…Recently, it has been reported that C. burnetii -specific T-cell IFN-γ release may represent a sensitive and long-lasting marker of past C. burnetii exposure ( Scholzen et al., 2021 ). The evaluation of cell-mediated responses to Coxiella through IFN-γ release assay (IGRA) could be very useful to detect past infections, since cellular response persists also in sero- and skin test-negative individuals ( Schoffelen et al., 2014a ; Schoffelen et al., 2013 ; Scholzen et al., 2021 ). It is still unknown which fraction of C. burnetii is responsible for IFN-γ release, but reported data show the existence of some immunodominant-specific peptides from its proteins that are recognized in IGRA-positive when compared with IGRA-negative subjects.…”
Section: Current Diagnostic Approaches For Coxiella Burnetiimentioning
confidence: 99%
See 1 more Smart Citation